Physical Activity, Eating Habits, Nutrition Knowledge and Nutritional Status of Central Obesity in Adolescents - Bohari, Bohari; Nabila, Miranda; Sijabat, Agnes Irma Yuliarta; Farendhiya, Andini; Tsany, Ridha Durati; Akta W, Uci Amelinda; Hidayah, Rahmah Nur; Setyaningsih, Putri; Anggini, Mutia Tri; Wulan Y. P, Yuniar (Media Publikasi Cendekia Indonesia, 2022)
Central obesity can occur in everyone from various age groups. One of the age groups that are prone to central obesity is adolescents. This study aims to determine the description of physical activity, diet, nutritional knowledge and nutritional status of adolescent central obesity. This type of research uses a quantitative descriptive method. The data collection time was carried out for 9 days starting on November 21, 2021 until November 29, 2021. The data was collected through interviews with research respondents and then the data was inputted into the KoBoToolbox application. The variables measured in this study were divided into several categories including characteristics, anthropometry, physical activity habits, eating habits, and respondents' knowledge. The results of the study are that there are 43.75% of adolescents who have central obesity, the physical activity of the respondents is included in the category of very rarely exercising by 46.88%, the frequency of consumption of junk food and fast food in a week is in the category of sometimes (2-3x/week). of 43.75%, the level of knowledge about obesity is included in the sufficient category, namely 60.94%. The conclusion is that adolescents have sufficient knowledge about obesity, but physical activity is still lacking and the habit of consuming risky foods such as junk food and fast food is high, and fiber consumption including less in a week